Identidade psicossocial, inserção social e saúde. O acesso de adolescentes à vida universitária visto por estagiários de psicologia - Vautero, Jaisso Rodrigues (2010)
Access to university life can be characterized as a way integration and social mobility for many teenagers. However, this vital way is threatened in many cases by doubts and uncertainties that arise. The assumption that drives this work is that these doubts and uncertainties relate to identity issues of adolescence. Such thoughts and feelings that present themselves before entering the university are in the relationship of self and his relationship with their significant others (Mead, 1972) and, in general, with its community. The doubts and uncertainties are permeate by social determinations that act on their subjectivity (Mezan, 1997) through the personal implications, familial, cultural, political, environmental, etc. From the assumption cited above, was created in the course of Psychology UFSM, a internship called Psychosocial Identity Clinic to work with graduate students and students of elementary and middle school. Regarding the latter, groups were created: 1) in partnership with the Municipality of Jaguari and the municipal Schools of that city, and 2) with the Colégio Técnico Industrial de Santa Maria (CTISM), which were denominated workshops identity during adolescence. The research revolves around these workshops, and plan to extend the understanding of the problematic identity of the participants in the groups of students in elementary and middle school offered, through the reports and discussions with the trainees (drivers of the groups) for the supervision of field and academic, held weekly. The methodology of training is based on the principles of action research as originally formulated by Kurt Lewin (1948), expanded from the study of works of John Dewey (in: DE FRANCO Pogrebinschi, 2008), where are based the groups discussion (Callejo, 2000). The research project is inspired by the same principles, and has as background materials produced by the trainees and the researcher's field diary. The method of analysis of the material is to confront the theoretical categories emerged and with previously established categories originate from the empirical material (E FERREIRA MOURA, 2005, Selltiz, 1975). The results point to the following areas: occupational identity, social inclusion and ingress into university life, psychosocial and Adolescent Identity, Ideology and Identity in Adolescence, Health and Identity. They are general thematic units coming most of them from material given to theoretical approach. The smaller units, called sub categories, came directly from the research data and are where the analysis happens. The conclusions is about three aspects: the first relates to issues of identity in relation to the adolescent's future prospects. The other axis refers to the university as a means of integration and social advancement, and finally, the implication is discussed and mediation.